التجارة وسيلة لوحدة الأمة الإسلامية: دراسة قرآنية تحليلية = Business as a way to strengthen the Unity of Muslim ummah - Mohamad, Nor Zatu Amni; Samsudin, Sofiah; Jani, Nazrul Affandi (Department of Quran and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, Malaysia, 2018)
The objective of this study is to enlighten the topic on business and Ummatic unity in the Holy Qur’an. This research uses the descriptive and analytical methods; by compiling the Qur’anic verses about business as a path to strengthen the Ummatic unity and revising them in the exegesis books, then to analyse them in order to arrive at the results. Among the most important findings of this research; the business in the Qur’an encourages the Ummah towards employment and acquiring the legal provisions. By the wisdom of Allah The Almighty, He makes analogies of the interactions between Him and humans using the words related to business so that the unseen rewards of afterlife become closer by comparing to the glimpsed profit of this world. This shows that it is very important for the Ummah to always remember their metaphysical transactions with their Lord -The Giver- every time they enter their physical transactions. The business must be taken as a way to strengthen the unity of the Muslim Ummah by striving towards the success in this world and in the hereafter, beautifying the characters, fighting the poverty, searching Allah’s bounties, preaching towards Allah and strengthening the relations between them.